Risks of acts of terrorism and specific features of their estimation - N. P. Tikhomirov; A. V. Novikov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies specific features of relatively new risks of declining the level of social and economic stability of states due to acts of terrorism and approaches to their estimation and prevention. Specificity of these risks are shown, which are connected with unlimited spheres of activity and methods of terrorists, vagueness of their reasoning and so on, which determines the high level of uncertainty in probability estimation, damages and other consequences of their activity. The structure of damages was systemized, within the frames of which direct and indirect damages in different fields of national economy and population of global community were identified. Estimation of such damaged which took place in different countries was provided. Unique characteristics of risks of terroristic attacks were given, which differ from other types of economic risks and predetermine the necessity to develop specific steps and strategies of their prevention. Key lines in the activity aimed at reducing risks of terroristic threats were discussed that stipulate disclosing basic factors promoting their appearance, estimation of conditions and trends in their development and elaboration of methods counteracting such threats. Legal basis of counteracting terrorism in the Russian Federation was considered that imply strengthening the role of state in the struggle against this phenomenon, for example by allocation of necessary finance resources directed to the development of accessible network of information, to the improvement of objects’ safeguarding, insurance protection of the population and other lines in anti-terrorist activity. The author discusses possible approaches to estimation of probability of terroristic attacks by using binary and multiple choice with regard to indicators showing conditions of their conducting.